THE DETERMINATION OF OPTICAL BAND AND OPTICAL CONSTANTS OF MnO2THIN FILMS PREPARED BY SPRAY PYROLYSIS - Salah K. Hazaa (Universitas Ahmad Dahlan, 2013)
Polycrystal MnO2thin films have been deposited using spray pyrolysis deposition technique under a varied thickness. By analyzing the X-ray diffraction, the structure of deposited films was found to be polycrystalline. Different optical properties of these films have been investigated by observing the optical absorption and transmission spectra. Various optical constants such as optical energy gap, the width of band tails of localized states into the gap, and steepness parameter, were calculated and the variation of various optical parameters such as refractive index, extinction coefficient and dielectric constant, with phonon energy are estimated.